An integrated conceptual model of visually impaired users' experience and technology acceptance of a website - Yazid, Mariam Azwa; Jantan, Azrul Hazri (World Academy of Research in Science and Engineering, 2019)
Internet has become one of the most important needs in our daily activity. It has benefited all its users inclusive the disabled community. There are wide spectrums of Internet’s disabled users. However, the aim of this paper is to present an integrated conceptual model focusing on understanding visually impaired users’ experience and technology acceptance of a website. This model will be used in further empirical study on modelling the relationship of visually impaired users’ experience and technology acceptance on web application. The evaluation of the model will be conducted using a pilot study. Series of questionnaire and structural equation modelling is expected to be used as tools for future. data collection and analysis.